Role of Government in Ensuring Safety Consciousness During Mineral Mining Activities in Nigeria - Emetumah, Faisal; Okoye, Anthony (European Scientific Journal, ESJ, 2018)
There are a lot safety issues bordering on events that are taking place in various mineral mining sites including destruction of lives, properties and environmental degradation which have been reported across Nigeria. These issues are further exacerbated because being aware of safety regulations and procedures does not necessarily imply that they will be adequately enforced or complied with. The study looked at the role of government in ensuring safety consciousness during mining activities in Nigeria, by identifying regulatory frameworks, enforcement and compliance issues as well as government mechanisms on safety during mining activities. Reviewed literature showed that there is no holistic regulatory framework on safety management; enforcement and compliance of safety regulations is plagued by corruption and ineptness. Safety issues were usually at the discretion of mining companies and implementing existing safety regulations was challenging and ineffective. The study concluded that the success or failure of government actions is vital in ensuring safety consciousness during mining activities in Nigeria. The study recommends a more comprehensive evaluation of environmental and safety consciousness during mining activities among others.